2008
DOI: 10.1136/bmj.39430.638241.ae
|View full text |Cite
|
Sign up to set email alerts
|

New onset and persistent symptoms of post-traumatic stress disorder self reported after deployment and combat exposures: prospective population based US military cohort study

Abstract: Objective To describe new onset and persistence of self reported post-traumatic stress disorder symptoms in a large population based military cohort, many of whom were deployed in support of the wars in Iraq and Afghanistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
452
8
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 559 publications
(501 citation statements)
references
References 29 publications
40
452
8
1
Order By: Relevance
“…Several studies have shown that exposure to stressful and traumatic events during military missions and combat is associated with an increased risk of post-traumatic stress disorder (PTSD) [1][2][3][4][5]. Rates of deployment-related PTSD, however, vary enormously between studies and countries, ranging from 1.5% to 31% in military personnel deployed to Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that exposure to stressful and traumatic events during military missions and combat is associated with an increased risk of post-traumatic stress disorder (PTSD) [1][2][3][4][5]. Rates of deployment-related PTSD, however, vary enormously between studies and countries, ranging from 1.5% to 31% in military personnel deployed to Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…They would also afford a better understanding of the costs of these conditions and the benefits of treatment so that the nation can make fiscally responsible investments in treatment and prevention programs. Some ongoing studies are examining these issues (Smith et al, 2008;Vasterling et al, 2006). However, they are designed primarily for a different purpose and thus can provide only partial answers.…”
Section: Invest In Research To Close Information Gaps and Plan Effectmentioning
confidence: 99%
“…Recent data available from the Department of Defense (DoD) (Hoge et al, 2004;Milliken, Auchterlonie, and Hoge, 2007;Smith et al, 2008) provide both predeployment and post-deployment data for these conditions. For example, Hoge et al (2004) examined Army and Marine personnel both before and after deployment, as well as their peers who were not deployed.…”
Section: Introduction Signature Woundsmentioning
confidence: 99%
“…In comparison with the general public and veterans not using the VA, veterans using VA services have also been shown to self-report poorer health [4][5][6]; are more likely to be physically inactive [2]; and are more likely to carry one or more chronic diagnoses such as hypertension, hypercholesteremia, and diabetes [2,4,[6][7]. Moreover, U.S. veterans who have spent time in theater often experience mental illnesses, pain syndromes, and musculoskeletal complaints [8][9][10][11][12]. These represent independent risk factors for sedentary behavior and obesity and are associated with increased morbidity and mortality [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently returned Operation Iraqi Freedom (OIF) and Operation Enduring Freedom (OEF) veterans represent a unique population served by the VA. Having recently been engaged in a physically demanding environment, these veterans, many with physical and/or mental sequelae from their tour of duty, face an abrupt transition to civilian life [11,[21][22][23][24][25][26][27][28]. In light of the growing body of evidence demonstrating the benefits of physical activity, including decreasing both obesity-associated morbidity and mortality [29][30] and disability from chronic musculoskeletal pain [31], OIF/OEF veterans using the VA are an ideal population for interventions centered around increasing physical activity.…”
Section: Introductionmentioning
confidence: 99%